Migrants, asylum seekers, and refugees: Different labels for immigrants influence attitudes through perceived benefits in nine countries - Graf, S.; Rubin, M.; Assilamehou‐Kunz, Y.; Bianchi, M.; Carnaghi, A.; Fasoli, F.; Finell, E.; Sendén, M. G.; Shamloo, S. E.; Tocik, J.; Lacko, D.; Sczesny, S. (European Journal of Social Psychology, 2023)
The world is witnessing the highest level of displacement of people on record. Public discourse often uses labels to describe people on the move such as ‘migrants’, ‘asylum seekers’, or ‘refugees’ interchangeably. A preregistered study in nine countries (Australia, the Czech Republic, Finland, France, Italy, Portugal, Sweden, Switzerland, and the United Kingdom; N = 2844) tested experimentally the effect of these three labels on attitudes towards immigrants and immigration policies. We found a significant difference between the label ‘migrant’ and both ‘asylum seeker’ and ‘refugee’ on the social distance scale. Participants were happier if migrants, rather than asylum seekers and refugees, were their neighbours, friends, or partners. The effect was mediated by perceived benefits, but not threats, whereby migrants were perceived to bring more benefits to receiving societies than asylum seekers and refugees. To increase the acceptance of immigrants, speakers may consider specifying the given group and emphasize benefits that immigrants bring to receiving societies.